Revisiting the Concept of Self-efficacy as a Language Learning Enhancer (GIST – Education and Learning Research Journal, 2018)
Individuals’ self-efficacy beliefs determine the ways they perform in any domain, since they reflect the extent to which people feel capable to achieve certain accomplishments Bandura (1997). This paper describes how a group of intermediate school students’constant failure in the exams, demotivating attitudes, apathy and reluctance to learn English as a foreign language, relate with their perceived capability, self-perception and their prior experiences as language learners. This descriptive and exploratory case study was developed in a private language centre and involved 11 participants. The goal of the study was to understand the causes of the students’ demotivation and reluctance to the language. For this purpose, autobiographies become a springboard to examine students’ language learning experiences. This information was analysed based on the grounded theory approach proposed by Freeman(1998), and findings reveal that the inadequate teachers’ discourse, classroom environment, rapport and feedback strategies influenced students’ perceived capability to perform in the English class. In addition, the data showed that the supportive role of parents and relatives, encouraged learners to adopt a resilient attitude with respect to the difficulties while learning the language.
Keywords: Self- efficacy beliefs; Students’ reluctance; autobiographies; teachers’role; EFL context